The model of eight cases in the dynamic assessment of an economic entity financial security - Andrzej Tokarski (Torun Business Review, 2016)
Among various types of enterprise security, the financial security constitutes the most important one. It can be explained by the fact that all the problems an enterprise deals with should be looked at from the point of view of finances, as all the enterprise activities have its reflection in them. In the market economy finances became a verifier whether the activities taken up by an enterprise are right and effective, both currently and in the future. Financial security became an important value each enterprise aims to achieve and then sustain, improve and guarantee. The purpose of this paper is to present a possibility to use the model of eight cases in the dynamic assessment of financial security of an economic entity. Analysis of the literature on the subject and the case study of an economic entity whose financial data were used to assess the financial security belong to the methods used in this publication.